Monitoring training load, recovery-stress state, immune-endocrine responses, and physical performance in elite female basketball players during a periodized training program - Nunes, J. A.; Moreira, A.; Crewther, B. T.; Nosaka, K.; Viveiros, L.; Aoki, M. S. (The Journal of Strength and Conditioning Research, 2014)
This study investigated the effect of a periodized training program on internal training load (ITL), recovery-stress state, immune-endocrine responses, and physical performance in 19 elite female basketball players. The participants were monitored across a 12-week period before an international championship, which included 2 overloading and tapering phases. The first overloading phase (fourth to sixth week) was followed by a 1-week tapering, and the second overloading phase (eighth to 10th week) was followed by a 2-week tapering. ITL (session rating of perceived exertion method) and recovery-stress state (RESTQ-76 Sport questionnaire) were assessed weekly and bi-weekly, respectively. Pretraining and posttraining assessments included measures of salivary IgA, testosterone and cortisol concentrations, strength, jumping power, running endurance, and agility. Internal training load increased across all weeks from 2 to 11 (p < 0.05). After the first tapering period (week 7), a further increase in ITL was observed during the second overloading phase (p < 0.05). After the second tapering period, a decrease in ITL was detected (p < 0.05). A disturbance in athlete stress-recovery state was noted during the second overloading period (p < 0.05), before returning to baseline level in end of the second tapering period. The training program led to significant improvements in the physical performance parameters evaluated. The salivary measures did not change despite the fluctuations in ITL. In conclusion, a periodized training program evoked changes in ITL in elite female basketball players, which appeared to influence their recovery-stress state. The training plan was effective in preparing participants for competition, as indicated by improvements in recovery-stress state and physical performance after tapering.